Analisis Visual Personal Branding Sisca Kohl di Instragram - Azharul Hakim; Poppy Febriana (Universitas Merdeka Malang, 2023)
The growth of creator content is a sign of how social media is developing, especially Instagram, which ranks fourth as social media with the most users. The presence of Instagram as a new medium is also able to build one's personal branding. Therefore, content creators must try hard to establish their brand image to be known. This research is a descriptive qualitative research. The descriptive method is used to find meaning, understanding, understanding of a phenomenon or event by being directly or indirectly involved in the object under study contextually and thoroughly. In this study, we will examine how the visualization of Sisca Kohl's personal branding on her Instagram account @siscakohl. This research refers to three visual research domains production site, self site, and audience site using Gillian Rose's visual methodology. The results of the study show that based on the results of analysis through content uploaded by Sisca on the @siscakohl Instagram account, it fulfills 5 personal branding laws out of 8 personal branding laws according to Montoya. namely specialization (the law of specialization), leadership (the law of leadership), difference (the law of distinctiveness), the law of visibility, unity (the law of unity). Of the 5 personal branding laws from Montoya, the most prominent are specialization (The Law of Specialization) and difference (the law of distinctiveness).